Characterization of the Effect of Photobiomodulation on Peripheral Blood Mononuclear Cells and Cd4+ T Cells from Healthy Donors and Multiple Sclerosis Subjects. - (:unkn) unknown (My University, 2020)
Multiple Sclerosis (MS) is a CD4+ T cell-mediated autoimmune demyelinating disease. The pathogenesis of MS is a combination of a pro-inflammatory autoimmune response coupled with nitrosative and oxidative stress. Mitochondrial dysfunction within the central nervous system (CNS) leads to a reduction of ATP and high concentrations of nitric oxide leads to the production of reactive oxygen and nitrogen species (ROS and RNS), resulting in oxidative and nitrosative stress that damages myelin and axons, leading to axonal loss and disease progression. Nitrosative stress is present in MS even in early stages of disease even before inflammation and the myelin destruction. The currently approved therapeutics to treat MS are effective at slowing disease progression but not preventing or reversing it, presumably because these strategies target the autoimmune response but do not address the accompanying oxidative/nitrosative stress. Photobiomodulation (PBM) is a therapeutic strategy shown to have to ameliorate chronic inflammatory and neurodegenerative conditions. During PBM, light is absorbed by cytochrome c oxidase (CCO) producing an increase in ATP production and improvement of mitochondrial function. Previously, our lab reported that 670nm light administered over the course of disease resulted in reduced IFN-ɣ, TNF-α, and nitrosative stress, and increased IL-4, IL-10, which correlated with the reduction in disease severity in the Experimental autoimmune encephalopathy (EAE) model of MS. Here, we evaluated the effect of PBM with different wavelengths of light administered at different doses on the immune response and nitrosative stress in MS subjects. The production of pro- and anti-inflammatory cytokines and the generation of nitrosative stress was measured in cell culture supernatants collected from peripheral blood mononuclear cells (PBMC) or isolated CD4+ T cells over the course of in-vitro treatment with light. The effect of PBM was dependent on the cell population (i.e., PBMC or CD4+ T cells); the wavelength of light; the dose of light administered; and severity of disease as assessed by the Patient Determined Disease Steps (PDDS) scale. The production of IFN-ɣ was higher by CD4+ T cells (735nm at 3J/cm2 and 10J/cm2) and PMBC (simultaneous 640/875/905nm, 1J/cm2 and 3J/cm2 in MS subjects with PDDS=0 compared to MS subjects with PDDS ≥1). Conversely, CD4+ T cells isolated from subjects with PDDS≥1 responded with higher levels of IL-10 compared with subjects with PDDS=0 after PBM treatment at 670nm (3J/cm2). Photobiomodulation was effective at reducing the generation of nitrite by cells isolated from subjects with MS compared to cells not receiving light treatment. The treatment of PBMC with 830nm (10J/cm2) resulted in reduced (p=0.0153) nitrite in comparison with controls (no light treatment). In addition, the effect of PBM with 830nm light on nitrite reduction correlated with the modulation of cytokines. Treatment of PMBC with 830nm light (10J/cm2) resulted in significantly reduced nitrite and increased IL-10 (p=0.0271). These same conditions likewise reduced IFN-ɣ produced by PBMC to a reproducible not statistically significant level (p=0.1940). The results to evaluate PBM on muscle fatigue showed that all MS subjects were able to recover strength within 12% of their initial strength after a single PBM treatment with the energy dose of 120J. Extended PBM treatment showed improvement in muscle recovery in some patients, however statistical significance was not achieved. The systemic effect of regional PBM therapy was assessed by measuring serum cytokines following light treatment. Most of the IFN-ɣ, IL-6 and IL-10 values on serum samples from MS subjects were below the limit of detection, which correlates with an absence of active disease. Values of TGF-β were lower in patients with higher disability status (PDDS≥1). The extended PBM treatment with the active device increased TGF-β levels in patients with higher disability status (PDDS≥1) compared to the inactive device, however, the increase was not significant. Collectively, the results presented show the potential of PBM to modulate immune response, reduce nitrosative stress, and improve muscle recovery. Future experiments with a more extended PBM treatment, subjects with higher disability status, and more sensitive methods to evaluate muscle recovery are needed.
Keywords: citokines; Light treatment; Multiple sclerosis; muscle fatigue; nitrosative stress; Photobiomodulation